Radioiodine Thyroid Ablation in Graves′ Hyperthyroidism: Merits and Pitfalls - J. Nwatsock; D. Taieb; L. Tessonnier; J. Mancini; F. Dong-A-Zok; O. Mundler (World Journal of Nuclear Medicine)
Ablative approaches using radioiodine are increasingly proposed for the treatment of Graves′ disease (GD) but their ophthalmologic and biological autoimmune responses remain controversial and data concerning clinical and biochemical outcomes are limited. The aim of this study was to evaluate thyroid function, TSH-receptor antibodies (TRAb) and Graves′ ophthalmopathy (GO) occurrence after radioiodine thyroid ablation in GD. We reviewed 162 patients treated for GD by iodine-131 (131 I) with doses ranging from 370 to 740 MBq, adjusted to thyroid uptake and sex, over a 6-year period in a tertiary referral center. Collected data were compared for outcomes, including effectiveness of radioiodine therapy (RIT) as primary endpoint, evolution of TRAb, and occurrence of GO as secondary endpoints. The success rate was 88.3% within the first 6 months after the treatment. The RIT failure was increased in the presence of goiter (adjusted odds ratio = 4.1, 95% confidence interval 1.4-12.0, P = 0.010). The TRAb values regressed with time (r = −0.147; P = 0.042) and patients with a favorable outcome had a lower TRAb value (6.5 ± 16.4 U/L) than those with treatment failure (23.7 ± 24.2 U/L, P < 0.001). At the final status, 48.1% of patients achieved normalization of serum TRAb. GO occurred for the first time in 5 patients (3.7%) who were successfully cured for hyperthyroidism but developed early and prolonged period of hypothyroidism in the context of antithyroid drugs (ATD) intolerance (P = 0.003) and high TRAb level (P = 0.012). On the basis the results of this study we conclude that ablative RIT is effective in eradicating Graves′ hyperthyroidism but may be accompanied by GO occurrence, particularly in patients with early hypothyroidism and high pretreatment TRAb and/or ATD intolerance. In these patients, we recommend an early introduction of LT4 to reduce the duration and the degree of the radioiodine-induced hypothyroidism.